Identification of renin inhibitors peptides from amaranth proteins by docking protocols - Nardo, Agustina Estefania (2020)
The objective of this work was to develop a new protocol to predict with greater confidence peptides as potential inhibitors of the renin enzyme. For this, free, friendly and rigorous servers developed specifically for peptides as ligands were used. Six peptides (SFNLPILR; FNLPILR; SFNLPIL; QAFEDGFEWVSFK; AFEDGFEWVSFK and VNVDDPSKA) identified in an amaranth hydrolysate obtained with alcalase (hydrolysis degree 21% ± 4) were used. Two positive (angiotensinogen and IRLIIVLMPILMA) and one negative (a tridecapeptide of alanine) controls were included in the analysis. A protocol was designed to include two consecutive stages was performed using CABS-dock server (http://biocomp.chem.uw.edu.pl/CABSdock) and FlexPepDock server (http://flexpepdock.furmanlab.cs.huji.ac.il/). Peptides SFNLPILR, FNLPILR and AFEDGFEWVSFK inhibited the enzyme in vitro. The heptapeptide FNLPILR was the most potent inhibitor, with an IC50 of 0.41 mM.